Oral bioavailability estimation of toxic and essential trace elements in PM10. (15th September 2019) - Moreda–Piñeiro, Jorge; Dans-Sánchez, Lucía; Sánchez-Piñero, Joel; Turnes-Carou, Isabel; Muniategui-Lorenzo, Soledad; López-Mahía, Purificación
Abstract: Oral bioavailability of essential and toxic elements has been assessed in particulate matter samples (PM10 ) at several sites (industrial, urban and sub-urban sites) by using an in-vitro model that combines simulated gastric/intestinal fluids and physiologically based extraction conditions which simulate human digestive system. Metals concentrations in bioavailable fractions will allow to a real human health-risk assessment associated to toxic metals. High oral bioavailability percentages were found for metals such as Cu, Mn, Ni, Pb and Sb (oral bioavailability ratios in the range of 39.7–45.7%). Al and V are less bioavailables (oral bioavailability ratios in the range of 1.8–9.2%). The influence of chemical composition (major ions, carboxylic acids and black carbon (BC)) on bioavailability ratios was assessed. Fe, Ni, V and Zn bioavailability ratios was found to be affected by the K +, NH4 +, acetate and BC contents of PM10 ; while a correlation was found between marine content (Cl − and Na + ) of PM10 and Cu, Fe and Mn dialyzability ratios. Zn and Sr bioavailability ratios were correlated with crustal contribution of PM10 . Principal Component Analysis (PCA) results also showed that Fe, Mn, Ni, Pb, Sb, Sr and V bioavailability are dependent on BC and NH4 + contents and Cu and Zn bioavailability are dependent on sea salt content of PM10 . Predicted bioavailability for some metals after applying a quadratic surface model based on crustal, marine and anthropogenic content of PM10 could also be established. Toxicity prediction of target metals, by using hazard quotient/index values, suggested potential non-carcinogenic risk for Pb and Sb. Graphical abstract: Image 1 Highlights: Oral bioavailability of metals in PM10 was assessed by a simulated dialysis method. High oral bioavailability ratios (∼40%) were assessed for Cu, Mn, Ni, Pb and Sb. Low bioavailability ratios (<10%) were assessed for Al and V. Major ions, carboxylic acids and BC contents affect metals bioavailability ratios. Hazard quotient/index values suggested potential non-carcinogenic risk for Pb and Sb.